2014
DOI: 10.1007/s40136-014-0045-x
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Extracapsular Dissection for Benign Parotid Tumors

Abstract: Surgical treatment of benign parotid tumors has been debated for decades. Extracapsular dissection (ECD) differs markedly from classic surgical approaches to the parotid neoplasm because facial nerve dissection is not performed. ECD, its advantages, disadvantages, indications, and contra-indications for benign tumors with an emphasis on benign mixed tumor will be comprehensively explored in this chapter. Factors noted to favor this approach include mobility of the tumor within the gland, a thin covering of cap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
27
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(29 citation statements)
references
References 45 publications
2
27
0
Order By: Relevance
“…26,29,30 Our study supports the hypothesis that partial parotidectomy techniques (FTD, ECD and LP) help reduce facial nerve dysfunction by limiting exposure of the facial nerve as compared to CSP and SP. 9,31,32 Of the techniques included in this study, FTD was associated with the lowest facial nerve injury rate. Koch et al 30 similarly found a significant correlation between the extent of the operation and the incidence of facial paresis (P = 0.01) and patient-perceived morbidity (P = 0.01) when comparing LP, CSP and SP.…”
Section: Discussionmentioning
confidence: 93%
See 4 more Smart Citations
“…26,29,30 Our study supports the hypothesis that partial parotidectomy techniques (FTD, ECD and LP) help reduce facial nerve dysfunction by limiting exposure of the facial nerve as compared to CSP and SP. 9,31,32 Of the techniques included in this study, FTD was associated with the lowest facial nerve injury rate. Koch et al 30 similarly found a significant correlation between the extent of the operation and the incidence of facial paresis (P = 0.01) and patient-perceived morbidity (P = 0.01) when comparing LP, CSP and SP.…”
Section: Discussionmentioning
confidence: 93%
“…CSP was traditionally considered the gold standard to treat and prevent recurrence, 7,9 however, many surgeons have adopted more conservative approaches such as ECD and LP for benign tumours. 1,4,9,11,14,18,24,28 The FTD technique (used in 21% of this study population) combines components of ECD, LP, and retrograde facial nerve dissection, aiming to minimize patient morbidity. In our cohort, FTD was associated with a 2.6% temporary facial palsy rate and 4% wound complication rate representing an adjusted OR of 0.19 and 0.16 respectively, compared to LP.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations